2014
DOI: 10.1021/ie4039828
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Uranium from Seawater by Amidoxime-Based Polymeric Adsorbent: Field Experiments, Modeling, and Updated Economic Assessment

Abstract: Uranium recovery from seawater has been investigated for several decades for the purpose of securing nuclear fuel for energy production. In this study, field column experiments have been performed at the Marine Sciences Laboratory of the Pacific Northwest National Laboratory (PNNL) using a laboratory-proven, amidoxime-based polymeric adsorbent developed at the Oak Ridge National Laboratory (ORNL). The adsorbent was packed either in in-line filters or in flow-through columns. The maximum amount of uranium uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
222
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(223 citation statements)
references
References 14 publications
1
222
0
Order By: Relevance
“…The recyclability of the adsorbent is a major factor which would justify further development of industrial scale extraction of uranium from seawater at a price competitive with those from conventional terrestrial ores. Kim et al . recently reported that a high capacity (6 g U/kg adsorbent) and durable (3 % loss/use) adsorbent could lead to a competitive seawater uranium production cost.…”
Section: Resultsmentioning
confidence: 99%
“…The recyclability of the adsorbent is a major factor which would justify further development of industrial scale extraction of uranium from seawater at a price competitive with those from conventional terrestrial ores. Kim et al . recently reported that a high capacity (6 g U/kg adsorbent) and durable (3 % loss/use) adsorbent could lead to a competitive seawater uranium production cost.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the most advanced technology for extracting the exceedingly dilute uranium (3.3 μg kg –1 , 14 nM)2 from seawater involves the use of polymeric sorbents functionalized with the amidoxime moiety (–C(NH 2 )NOH) 3,4. Promising marine test results have been reported in Japan over a decade ago in which the uranium uptake was 1.5 g U kg –1 sorbent after 30 days5 while more recently, marine tests conducted in the United States revealed that 3.3 g U kg –1 sorbent was obtained after 8 weeks 6…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This menace stimulates a survey of the efficient, rapid and cost-effective methods for the elimination, monitoring and determination of uranium ions, particularly in contaminated water samples to be very important. [4][5][6] The low concentration of uranium ion in the presence of relatively high concentrations of other ions causes difficulties in its direct determination.…”
Section: Introductionmentioning
confidence: 99%